INTERPETASI MODERN TENTANG TEORI DAN FILOSOFIS PENELITIAN - Elia Radianto (KRITIS, 2023)
In practice, scientific research methods are often based on assumptions that are guided by paradigms that describe a philosophical belief in guiding an action to overcome problems in research. Before the discovery of the mixed method, there was a quantitative method with a positivist paradigm (positivism) and a qualitative method with a post-positivist paradigm. However, in the development at the end of the 1980s until now, the mixed method has been widely used and seen as a new methodology that invites debate, especially related to philosophical, procedural development, and expansion to become different disciplines. Therefore, the author offers the Utilitarianism Paradigm – Elia Radianto Version (PU-VER), as a new paradigm that can be used to base the mixed method. Thus, there are currently three research methods, which have the main paradigm, namely: 1) quantitative with a positivist paradigm (positivism); 2) qualitative with post-positivism or constructivist (interpretative) paradigms or in some textbooks referred to as naturalistic or phenomenological paradigms; and 3) mixed methods with Paradigm Utilitarianism-Versi Elia Radianto (PU-VER).